Self adaptive method for end-to-end available bandwidth estimation - ZHOU An-fu; LIU Min; LI Zhong-cheng; XIE Gao-gang (Tongxin xuebao)
A low overhead, self adaptive method for end-to-end available bandwidth estimation was proposed. Firstly, on low utilization path, the mathematic equation between the probability that input probe gap increases caused by CT pack-ets and the distribution of output probe gap was set up, and then CT load was derived from the equation. Secondly, a met-ric called gap symmetry （GS） was proposed to weigh the busyness degree of a network path, and the self adaptive avail-able bandwidth estimation method based on GS was presented. NS-2 simulations show that compared with previous methods, our method shows its advantages in terms of measurement time, accuracy, and overhead.